Reactive Oxygen Species in Macrophages: Sources and Targets - Canton, Marcella; Sánchez-Rodríguez, Ricardo; Spera, Iolanda; Venegas, Francisca C.; Favia, Maria; Viola, Antonella; Castegna, Alessandra (Frontiers in Immunology, 2021)
Reactive oxygen species (ROS) are fundamental for macrophages to eliminate invasive microorganisms. However, as observed in nonphagocytic cells, ROS play essential roles in processes that are different from pathogen killing, as signal transduction, differentiation, and gene expression. The different outcomes of these events are likely to depend on the specific subcellular site of ROS formation, as well as the duration and extent of ROS production. While excessive accumulation of ROS has long been appreciated for its detrimental effects, there is now a deeper understanding of their roles as signaling molecules. This could explain the failure of the “all or none” pharmacologic approach with global antioxidants to treat several diseases. NADPH oxidase is the first source of ROS that has been identified in macrophages. However, growing evidence highlights mitochondria as a crucial site of ROS formation in these cells, mainly due to electron leakage of the respiratory chain or to enzymes, such as monoamine oxidases. Their role in redox signaling, together with their exact site of formation is only partially elucidated. Hence, it is essential to identify the specific intracellular sources of ROS and how they influence cellular processes in both physiological and pathological conditions to develop therapies targeting oxidative signaling networks. In this review, we will focus on the different sites of ROS formation in macrophages and how they impact on metabolic processes and inflammatory signaling, highlighting the role of mitochondrial as compared to non-mitochondrial ROS sources.